Heat versus altitude training for endurance performance at sea level - Baranauskas, M. N.; Constantini, K.; Paris, H. L.; Wiggins, C. C.; Schlader, Z. J.; Chapman, R. F. (Exercise and Sport Sciences Reviews, 2020)
Environmental stressors, such as heat or altitude, elicit dissimilar physiological adaptations to endurance training programs. Whether these differences (i.e., increased hemoglobin mass vs plasma volume) differentially influence performance is debated. We review data in support of our novel hypothesis, which proposes altitude as the preferred environmental training stimulus for elite endurance athletes preparing to compete in temperate, sea-level climates (5°C-18°C).